Association of dyslipidemia with diabetic retinopathy in type 2 diabetes mellitus patients: A hospital-based study - Kalaimamani Ezhilvendhan; Anitha Sathiyamoorthy; B Jey Prakash; B Saravana Bhava; Arjun Shenoy (Wolters Kluwer Medknow Publications, 2021)
Background: Dyslipidemia is an important risk factor that can lead to the progression of retinopathy (DR). Diabetic dyslipidemia with low high-density lipoprotein (HDL) and increased triglycerides (TGs) are seen frequently among Type 2 diabetic mellitus. Aims and Objectives: (1) To assess the level of serum lipids (total cholesterol, TGs, HDL, and low-density lipoprotein [LDL]) among type 2 diabetes patients. (2) To determine the association between serum lipid levels and DR. Materials and Methods: This was a hospital-based cross-sectional study conducted in a tertiary care hospital in Salem from September 2018 to March 2020 with a sample size of 200. Details of their diabetic history were obtained. Patients were evaluated for their HbA1C levels, hypertension, and lipid profile status. Early treatment DR Study system was used to classify DR. Low density lipoprotein cholesterol was calculated by Freidewald's equation. Results: This study showed a significant association among DR and LDL cholesterol. DR with raised LDL, TGs levels, and lowered HDL on adjusted analysis. There was strong association between DR and serum cholesterol in unadjusted analysis; however, there was no association when adjusted for factors such as age, gender, duration of diabetes, and glycemic control. Majority of participants were males (57.5%) with a male: female = 1.35:1. The mean age of the patients in our study was 57.8 (5.8) years and 54.4 (6.6) years in patients with DR and patients without retinopathy, and it was found to be statistically significant. There was a significant difference in the duration of diabetes with the presence of DR and the patients with DR were having longer duration of diabetes (7.9 vs. 6.2 years; P < 0.001). Moderate nonproliferative diabetic retinopathy (NPDR) was found to be present in 41.0% of eyes followed by mild NPDR (20.5% eyes). Proliferative diabetic retinopathy was present only in 9.5%, and the severity of retinopathy was associated only with the HDL level, and there was no association found with total cholesterol, TG, and LDL cholesterol. Conclusion: A statistically significant correlation was found between dyslipidemia and the severity of DR among Type 2 diabetic patients.